Insolvency Reforms in India: Policy and Economic Implications - Vig, Shinu (The journal of contemporary issues in business and government, 2019)
The Indian government introduced the Insolvency and Bankruptcy Code of India (IBC) in 2016 as reforms in insolvency and bankruptcy laws are crucial for improving the business environment and credit markets in India. The banking sector of India has been marred for long by the problem of Non-performing-Assets (NPAs), and many of its largest companies are struggling under massive debts. The main objective of the new law was to facilitate insolvency resolution and liquidation in a timely manner and to improve India’s ranking in the ‘ease of doing business’ index. This paper highlights the importance of insolvency reform in the economic policy of any country, while it examines the insolvency regime in India under the IBC with respect to its prospects and challenges and implications of the Code for the Indian corporate sector. Thus, the paper contributes to the policy debate relating to this subject.